1997
DOI: 10.1021/ic9613366
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Main-Group Metal Ions by Electrospray Mass Spectrometry. 1. Investigation of Aqueous Polyselenide Species and Effects of Cations and pH

Abstract: Polyselenide anion speciation in aqueous solution has been investigated by electrospray mass spectrometry (ESMS). Two methods of control over this speciation are reported: countercation substitutions and pH adjustments. The countercation has been found to affect the degree of disproportionation or comproportionation. Solutions of sodium tetraselenide displayed numerous Se n 2and HSe n -species in neutral and basic soluions. In potassium solutions, the dominant species was Se 4 2-‚H 2 O. Solutions of cesium pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 53 publications
2
24
0
5
Order By: Relevance
“…The existence of a (Se 5 ) 2– species in solution was determined by electrospray ionization mass spectroscopy (ESI‐MS) and further studies on pH dependencies and the impact of different counterions were elucidated by Dorhout and co‐workers 74. However, further mass spectrometric data have not been reported to date.…”
Section: Spectroscopic Data and Propertiesmentioning
confidence: 99%
“…The existence of a (Se 5 ) 2– species in solution was determined by electrospray ionization mass spectroscopy (ESI‐MS) and further studies on pH dependencies and the impact of different counterions were elucidated by Dorhout and co‐workers 74. However, further mass spectrometric data have not been reported to date.…”
Section: Spectroscopic Data and Propertiesmentioning
confidence: 99%
“…We now report the preparation and structure of Cs 6 Sb 4 Se 9 Á0.5H 2 O, which contains the novel discrete [Sb 4 Se 9 ] 6À chain anion ( Fig. 1) not found by Raymond et al (1997) for the K + /Sb/Se system. Three caesium selenidoantimonates, CsSbSe 2 (Kanishcheva et al, 1980), CsSb 2 Se 4 (Sheldrick & Kaub, 1986) and Cs 3 Sb 5 Se 9 (Sheldrick & Hä usler, 1988) had been structurally characterized prior to this study.…”
Section: Commentmentioning
confidence: 95%
“…Although electrospray mass spectrometric measurements on the K + /Sb/Se system in dimethylformamide (DMF) have confirmed the presence of the corner-bridged oligomeric anions [Sb 2 Se 5 ] 4À (Raymond et al, 1997) 6À , only the first of these selenidoantimonate(III) anions has been characterized in the solid state. Both [Fe(en) 3 ] 2 Sb 2 Se 5 (en = ethylenediamine) (Chen et al, 2000) and [Mn(en) 3 ] 2 Sb 2 Se 5 (Nä ther et al, 2003) contain discrete [Sb 2 Se 5 ] 4À anions comprising two corner-bridged SbSe 3 pyramids.…”
Section: Commentmentioning
confidence: 99%
“…On dissolving selenium to saturation under anoxic conditions, the major aqueous species are the HSe – anion at 5 < pH < 8 and Se 4 2– at 9 < pH < 13 in the presence of Na + ions 44. Electrospray MS studies45 have indicated that Se 5 2– anions may also be present at low concentrations in saturated aqueous polyselenide solutions above pH 9 and have confirmed Se 4 2– as the dominant species, regardless of the nature of the alkali metal cation (A = Na + , K + , Cs + ). Individual selenium atoms of an Se n 2– anion can be readily probed by 77 Se NMR, as their chemical shifts increase with distance from the chain end and lie within the wide δ range of 192–860 relative to δ(Me 2 Se) = 0 46.…”
Section: Polychalcogenide Anionsmentioning
confidence: 99%